2010
DOI: 10.1039/c0nj00301h
|View full text |Cite
|
Sign up to set email alerts
|

Chloroindate(iii) ionic liquids as catalysts for alkylation of phenols and catechol with alkenes

Abstract: Chloroindate(III) ionic liquids are shown to be versatile catalysts for the alkylation of phenols with alkenes, giving high conversions to alkylated phenols with high selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Ionic liquids based on other metals, in particular chloroindate(III) and chlorozincate(II) systems, are often described as moisture-stable alternatives to chloroaluminate(III) systems. 146,147 Indeed, chloroindate(III) and chlorozincate(II) ionic liquids can be used in the open air and, moreover, are less oxophillic than the Al(III)-based analogues. This can be used to advantage, for example as catalysts for reactions of alcohols or phenols 146,148 which are incompatible with chloroaluminate(III) ionic liquids.…”
Section: Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids based on other metals, in particular chloroindate(III) and chlorozincate(II) systems, are often described as moisture-stable alternatives to chloroaluminate(III) systems. 146,147 Indeed, chloroindate(III) and chlorozincate(II) ionic liquids can be used in the open air and, moreover, are less oxophillic than the Al(III)-based analogues. This can be used to advantage, for example as catalysts for reactions of alcohols or phenols 146,148 which are incompatible with chloroaluminate(III) ionic liquids.…”
Section: Hydrationmentioning
confidence: 99%
“…This is exemplified by the alkylation of benzene using p-formaldehyde 184 However, despite (or because of) the extreme activity of chloroaluminate(III) systems, it is often beneficial to move onto milder catalysts. Gunaratne et al 186 showed how phenols and catechols could be alkylated in weakly acidic chloroindate(III) ionic liquids, with good control over selectivity, preventing polyalkylation that would occur using stronger acids. Moreover, chloroindate(III) did not react with hydroxo groups of the reactants, which is a major impediment for using chloroaluminate(III) systems in such reactions.…”
mentioning
confidence: 99%
“…Chloroindate(III) ionic liquids are hydrolytically stable [63] and mildly Lewis acidic [27], which contrasts with systems based on lighter icosagenes, and opens up new application routes, such as: transesterification (biodiesel synthesis) [64], alkylation of phenols or catechols with alcohols [63], as well as for the protection of alcohols, followed by their conversion to acetates and trimethylsilyl ethers [65]. Noteworthy, in some instances compositions with excess of InCl 3 are used (v InCl3 [ 0.50), even though they form a suspension/paste, rather than the ionic liquid [66] [37,38].…”
Section: Chloroaluminate(iii) Ionic Liquidsmentioning
confidence: 99%
“…Published attempts to overcome this major limitation include the application of less oxophilic, acidic chloroindate ionic liquids15 and the use of Brønsted acidic ionic liquids 16. The utility of chloroindate melts has been demonstrated by Seddon et al for the alkylation of phenol and catechol with alkenes15,17 and by Leitner et al for the reaction of anisole and acetic anhydride 18. The use of Brønsted acidic ionic liquids has been realized by Sesing et al for the Fries rearrangement19 and by Ignatiev et al for the dehydration of cyclohexanol 20.…”
Section: Introductionmentioning
confidence: 99%